New Frontiers in Travel Motivation and Social Media: The Case of Longyearbyen, the High Arctic - Carolina Aldao; Tanja A. Mihalic (Sustainability, 2020)
Tourism explores new frontiers by traveling around unknown geographical and technological territories that bring new tourism opportunities and hazards to satisfy visitors’ needs and sustainability and responsibility in destinations. This study introduces a composite model for measuring travel motivation and the impact of social media on travel behavior and applies it to the town of Longyearbyen in the High Arctic. Both aspects were surveyed through qualitative semi-structured visitor interviews. While the motivation to visit Longyearbyen depended on travelers’ needs, their travel experiences, and push and pull motivational factors, respondents gave examples of how social media positively or negatively affected different elements of their motivation and visitation. The study indicates the opportunities and hazards analyzed from social media as well as future research directions needed in the pursuit of a more responsible tourism approach while exploring new technological and geographical frontiers.